Evidence-Based Case Report: Pengaruh Penerapan Pijat Sakrum Dan Pijat Endorfin Terhadap Nyeri Persalinan Kala 1 - Athiyah Fauziyyah Hafizhah; Diyan Indrayani; Sri Mulyati (LPPM STIKes BHAKTI HUSADA CIKARANG, 2026)
As the time of delivery approaches, mothers tend to feel anxious. If not managed properly, this can worsen labor pain, thereby increasing the risk of complications. To address this, massage can be given during the first stage of labor as an effort to reduce labor pain, thus providing a positive childbirth experience. The purpose of this study is to analyze the effect of sacral massage and endorphin massage on reducing pain during the first stage of labor. The research design used a case study with an Evidence-Based Case Report (EBCR) approach, by reviewing supporting articles from databases published between 2020 and 2025. The intervention was carried out on a single case, namely Mrs. A, a mother in the first stage of labor, who was given sacral massage during contractions and endorphin massage when not in contraction for 30 minutes. Pain evaluation was conducted using the visual analog scale (VAS). The intervention results showed that Mrs. A, during the labor phase, with sacrum massage and endorphin massage, was able to reduce her pain; however, due to fatigue, she was referred to the hospital. The labor process at the hospital proceeded spontaneously without complications. Thus, efforts to reduce labor pain with sacrum massage and endorphin massage have been proven effective and are recommended as one of the pain relief methods.